Intraperitoneal injection of ginkgolide B, a major active compound of Ginkgo biloba, dose-dependently increases the amount of wake and decreases non-rapid eye movement sleep in C57BL/6 mice. (23rd March 2020) - Nishimon, Shohei; Yamaguchi, Mai; Muraki, Hisae; Sakai, Noriaki; Nishino, Seiji
Highlights: Effects of ginkgolides and bilobalide were examined on sleep/wake stages in mice. Ginkgolide B is a compound of the Ginkgo biloba extract. This extract is produced from the ginkgo tree leaves. Ginkgolide B dose-dependently increases the amount of wake and decreases that of NREM. Abstract: The terpene lactones of Ginkgo biloba extract, namely ginkgolides (A, B, and C) and bilobalide, possess antioxidant, anti-inflammatory, and neuroprotective effects. They are widely prescribed for the treatment of cerebral dysfunctions and neurological impairments. In addition, they demonstrate antagonistic action at the gamma-aminobutyric acid type A and glycine receptors, which are members of the ligand-gated ion channel superfamily. In the present study, the effects of ginkgolides (A, B, and C) and bilobalide on sleep in C57BL/6 mice were investigated. Ginkgolide B was found to dose-dependently increase the amount of wake and decrease that of non-rapid eye movement sleep without changes in the electroencephalography power density of each sleep/wake stage, core body temperature and locomotor activity for the first 6 h after intraperitoneal injection. Of note, the amount of wake after injection of 5 mg/kg of ginkgolide B showed a significant increase (14.9 %) compared with that of vehicle ( P  = 0.005). In contrast, there were no significant differences in the amount of sleep, core body temperature, and locomotor activity in the mice injected with ginkgolide A and C. Bilobalide briefly induced a decrease in locomotor activity but did not exert significant effects on the amounts of sleep and wake. The modes of action of the wake-enhancing effects of ginkgolide B are unknown. However, it may act through the antagonism of gamma-aminobutyric acid type A and glycine receptors because it is established that these inhibitory amino acids mediate sleep and sleep-related physiology. It is of interest to further evaluate the stimulant and awaking actions of ginkgolide B on the central nervous system in clinical and basic research studies.